Which equation matches the function shown in the graph?A. Y= sin(x-pi)+3
B. Y= 3cos(x+pi)
C. Y= 3sin(x-pi)
D. Y= 3cos(x-pi)
Which equation matches the function shown in the graph? A. - 1

Answers

Answer 1
Answer:

Option C is correct. The equation that matches the function shown in the graph is expressed as y = 3sin(x-π)

The general formula for a sine function is expressed as;

y = Asin(x+Ф)

A is the amplitude i.e the maximum point on the curve. From the diagram, we can see that the maximum point is at 3 (factor 3 elongates the curve).

A = 3

Also, since the graph translates to the right by π, hence Ф = -π

Substituting the resulting values into the formula, we will have;

y =3sin(x+ (-π))

y = 3sin(x-π)

Hence the equation that matches the function shown in the graph is expressed as y = 3sin(x-π)

Learn more about since graph here: brainly.com/question/16262155

Answer 2
Answer:

Answer:

its c ! just took the test :)


Related Questions

Which of the following phases translate to the expression y+7
How do you simplify pxqx4
F(x)=x2−x−1f, left parenthesis, x, right parenthesis, equals, x, squared, minus, x, minus, 1 What is the average rate of change of fffover the interval -1\leq x\leq 1−1≤x≤1minus, 1, is less than or equal to, x, is less than or equal to, 1?
How do you know that 4x2x2 is the same as 4x4
Which table corresponds to the function y=-3x+5

PLEASE HELP! I WILL MARK BRAINLIEST!!! What are the essential elements of an independent clause?

a subject and a complete thought
a subject, a verb, and a complete thought
a verb and a complete thought
a complete thought

Answers

Answer: A subject, a verb, and a complete thought.

Step-by-step explanation:

                    Independent clauses have three components:

  • They have a subject - they tell the reader what the sentence is about.
  • They have an action or predicate - they tell the reader what the subject is doing.
  • They express a complete thought - something happened or was said.

Step-by-step explanation:

A subject, a verb, and a complete thought

Feet12. Darcy and Danny were diving on a trip in
the Bahamas. When they stopped to look at a
school of fish, Darcy was 178 feet below the
surface of the water, and Danny was
2
feet
below the surface. Who was closest to the
is
Ire
surface of the water

Answers

Danny was closest to the surface of the water.

Here,

Darcy and Danny were diving on a trip in the Bahamas.

When they stopped to look at a school of fish, Darcy was √(78) feet below the surface of the water and Danny was 17/2 feet below the surface.

What is square root?

A square root of a number x is a number y such that y2 = x.

Now,

Darcy was √(78) feet below the surface of the water.

√(78) = 8.83

Danny was 17/2 feet below the surface.

(17)/(2) = 8.5

Clearly,  8.5 < 8.85

Hence, Danny was closest to the surface of the water.

Learn more about the square root visit:

https://brainly.in/question/28093691

#SPJ2

Here’s the answer; it’s just a case of finding the two values and comparing them.

HELP HELP HELP HELP HELP HELP WINNER GETS 8 points

Answers

do you know how to find the area of a normal shape?
You can split this shape into 2 rectangles if you draw a horizontal line between the bigger and smaller rectangle. 
The top half
LxW=A
5x7=35
The top half's area is 35.
The bottom Half
LxW=A
10x8=80
Now, add these 2 areas together and that is your answer.
Your answer is 115 cm^2

Which problem is equivalent to 12/18A
18 ÷ 12

B
12 ÷ 18

C
12 x 18

D
12 x 12 x 18

Answers

Answer:

B

Step-by-step explanation:

What is estimate 4.23-2.51

Answers

the answer is 1.72 and it would be 2 if u estimated
I just subtract 4.23-2.51 then I got the answer
the answer is 1.72

Let be the integers a,b,c with a^2-4b=c^2

To be shown that the number a^2-2b can be written as a sum of 2 perfect squares.

Answers

a^2 - 4b = c^2 <=> a^2 - c^2 = 4b <=> ( a + c )( a - c ) = 4b, cu a, b, c nr. intregi ;
Avem doua posibilitati :
a) a = 2x si b = 2y;
Atunci ( a + c )( a - c ) = 4b <=> x^2 - y^2 = b;
Relatia  a^2 -2b devine 2x^2 +2y^2 = (√(2) x)^2 + (√(2) y)^2, adica suma a doua patrate perfecte ;

b) a = 2x + 1 si b = 2y + 1 ;
In mod analog. obtii ca x^2 - y^2 + x - y = b;
si, dupa ce prelucrezi, ai ca a^2 - 2b = [√(2) ( x + 1 / 2 )]^2 + []√(2) ( y + 1 / 2 )^2, adica, suma a doua patrate perfecte .

Bafta!


{ a }^( 2 )-4b={ c }^( 2 )\n \n { a }^( 2 )-4b+2b={ c }^( 2 )+2b\n \n { a }^( 2 )-2b={ c }^( 2 )+{ \left( \sqrt { 2b }  \right)  }^( 2 )

b={ 2 }^( n )\n \n n>0

(n) is the set of odd natural numbers greater than 0.